Association between aerobic fitness and the functional connectome in patients with schizophrenia - Röll, Lukas; Maurus, Isabel; Keeser, Daniel; Karali, Temmuz; Papazov, Boris; Hasan, Alkomiet; Schmitt, Andrea; Papazova, Irina; Lembeck, Moritz; Hirjak, Dusan; Sykorova, Eliska; Thieme, Cristina E.; et al. (European archives of psychiatry and clinical neuroscience, 2022)
Schizophrenia is accompanied by widespread alterations in static functional connectivity associated with symptom severity and cognitive deficits. Improvements in aerobic fitness have been demonstrated to ameliorate symptomatology and cognition in people with schizophrenia, but the intermediary role of macroscale connectivity patterns remains unknown.